2013
DOI: 10.1161/circulationaha.113.002539
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Determinants of Implantable Cardioverter Defibrillator Deployment Among Primary Prevention Candidates With Subsequent Sudden Cardiac Arrest in the Community

Abstract: Background-The prevalence rates and influencing factors for deployment of primary prevention implantable cardioverter defibrillators (ICDs) among subjects who eventually experience sudden cardiac arrest in the general population have not been evaluated. Methods and Results-Cases of adult sudden cardiac arrest with echocardiographic evaluation before the event were identified from the ongoing Oregon Sudden Unexpected Death Study (population approximately 1 million). Eligibility for primary ICD implantation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 33 publications
2
69
0
1
Order By: Relevance
“…In fact, ICD recipients were older and had a greater comorbidity burden compared with nonrecipients. Of note, the mean age of our older Asian ICD recipients (63 years) was comparable to the younger Western ICD recipients (61 to 67 years) reported, 41,42 emphasizing the growing concern that HF afflicts Asians at a younger age than their Western counterparts. 13,43 A high proportion (79.1%) of ICDeligible patients were male, and among ICD recipients, an even higher proportion (83.5%) were male.…”
Section: Clinical Factorssupporting
confidence: 55%
“…In fact, ICD recipients were older and had a greater comorbidity burden compared with nonrecipients. Of note, the mean age of our older Asian ICD recipients (63 years) was comparable to the younger Western ICD recipients (61 to 67 years) reported, 41,42 emphasizing the growing concern that HF afflicts Asians at a younger age than their Western counterparts. 13,43 A high proportion (79.1%) of ICDeligible patients were male, and among ICD recipients, an even higher proportion (83.5%) were male.…”
Section: Clinical Factorssupporting
confidence: 55%
“…Their retrospective population-based evaluation found that only 13% of previously ICD-eligible individuals who suffered sudden cardiac arrest had received ICD therapy for primary prevention. 9 The experience in our study demonstrates that although the allocation of ICD therapy may be far from perfect for the population at large, ICD use is more efficient in the higher-risk population of known CAD and persistently depressed LVEF.…”
Section: Discussionmentioning
confidence: 79%
“…So in response to the second question, although initiatives that increase ICD use in patients who meet present guidelines have the potential to save lives, the data by Narayanan et al 6 illustrate the potential ceiling to the absolute number of lives that can be saved with this approach. To further influence mortality from SCA, we need to focus effort, research, and resources on multiple strategies aimed at SCA prevention at earlier stages and in populations at all levels of risk.…”
Section: Circulationmentioning
confidence: 99%